Narrative of the Anti-Soviet Partisan War: a Family Case - Paskočiumaitė, Greta (Tautosakos darbai, 2022)
The subject of the article is the narrative of the partisan war maintained by family members of the partisans from the Vytis Partisan District Antanas Žilys and Zofija Žilienė. This case study aims at revealing the memory of struggle for freedom from the perspective of the families that had lived prior to the beginning of the anti-Soviet resistance. It includes circumstances under which the narrative was shaped, the peculiarities of its content and change, its influence on the personal attitudes of the family members and the fundamentals of its transferring from one generation to another. Stories recorded in 2019–2020 embrace three generations of the family: Algimantas the son of the partisans, Jurga and Gediminas their grandchildren, and Gaudutė their great-granddaughter. In order to perceive the background of the story, the author uses memoirs by the freedom fighters connected to the Žiliai Family, and by Zofija Žilienė, published at the onset of the Lithuanian independence. According to the author, a person telling his / her life story or relating its separate events presents an original interpretation of the past and shapes his / her identity; therefore, such narrative is of utmost importance in terms of understanding the partisans and their closest surroundings. The members of the partisan community exhibit a remarkably positive attitude towards the Žiliai Family, both because of their resistance activities and their personal traits. Published memoirs and artistic works by the partisans depict not only Antanas and Zofija but also their three children who had to grow up with a number of foster-parents. According to their former brothers in arms and family members, the family ties were damaged during the partisan war, albeit still partly maintained, since the parents used to visit their children, contributing to their upbringing. After Antanas was killed in May of 1949, and Zofija subsequently arrested, the family ties weakened even more; however, the narratives preserved in the memory of family members assume that the experiences of resistance and repressions as well as similar reaction towards them bounded them all together. The study revealed that the partisan war and Antanas’ death became subjects of a more open discussion in the family only in the eve of the Lithuanian independence in the 90s, although during the Soviet occupation the family members had already intuitively felt a complicated history lurking behind. It should be noted, however, that the memories of the partisan war are not merely directly transferred: the narrative is shaped considerably by certain omissions and by the family members’ behavior during the Soviet period, attempting by various means to shield their close ones from the attention of Soviet repressive structures. According to their narratives, every member of the Žiliai Family appreciates freedom as the main value of life, although painful experiences have forced Zofija and her son Algimantas to adapt to the Soviet regime. However, stories by Zofija’s grandchildren clearly exhibit their subconscious desire to oppose the system and longing for the independence. All narrators seem to be proud of their family members’ involvement in the struggle for freedom, despite their understanding of the cruel impact it had on the family life. Knowledge of the family history is valued as a responsibility to be passed on and appreciated. The younger the generation, the more remote its connections to the resistance; this enhances their impartiality and a lack of authentic experience. Grandchildren of the partisans already tend to speak more openly about the painful experiences of their family members, thus revealing the complicated reality of the struggle for freedom. Narratives by the partisans’ son display clear traces of immediate communication with the partisans, including details from their everyday life and connections with their families, as well as authentic memories of the family relationship. Algimantasʼ mind is more occupied by the image of his slain father. Subsequent generations have mostly preserved memories of interactions with Zofija, supplementing her stories with their own insights in the partisan struggle and attitude towards the Soviet regime. The chief storyteller in the family is still Algimantas, sharing his parents’ and his own experiences both with the family and with the general public. The study reveals that experiences of resistance and repression have influenced the self-perception of several generations. The narrative preserved by the partisan families expands the notion of their fight and supplements the history of struggle for freedom with new and significant details.